Toxic Masculinities in Post-9/11 Islam-Themed French Novels: Plateforme and Syngué Sabour. Pierre de Patience - Wening Udasmoro (k@ta: A Biannual Publication on the Study of Languange and Literature, 2022)
ABSTRACT This article aims to explore the concept of toxic masculinities in two French literary works, namely Plateforme by Michel Houellebecq and Syngué Sabour. Pierre de Patience by Atiq Rahimi, whose stories are related to Islam after the September 11, 2001 tragedy. Toxic masculinities are suspected to be present in both works, namely by placing women in the position of objects of sexual gaze and symbolic violence. This article dredges the concept of toxic masculinities, which is a derivation of the concept of hegemonic masculinities introduced by Raewyn Connell. This paper employs a critical discourse analysis method by examining the language used by the authors at levels of linguistic practice, discursive practice, and social practice with corpus data taken from the wordings and rewordings of the texts. This paper concludes that sexual gaze and symbolic violence are toxic because they can be drivers of physical violence. Keywords: toxic, masculinities, French literature, Islam